2020
DOI: 10.1038/s41598-020-58315-w
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine induces Parkin-independent mitophagy through mitochondrial-resident E3 ligase MUL1-mediated stabilization of PINK1

Abstract: Mitophagy plays an important role in the maintenance of mitochondrial homeostasis. PTEN-induced kinase (PINK1), a key regulator of mitophagy, is degraded constitutively under steady-state conditions. During mitophagy, it becomes stabilized in the outer mitochondrial membrane, particularly under mitochondrial stress conditions, such as in treatment with uncouplers, generation of excessive mitochondrial reactive oxygen species, and formation of protein aggregates in mitochondria. Stabilized PINK1 recruits and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…These findings suggest that MITOL ubiquitinates and subsequently degrades Parkin in a proteasome‐dependent manner. To understand whether the ubiquitination of Parkin by MITOL has a functional effect on mitophagy, we performed quantitative analysis of mitophagy using the mitochondria‐localized pH‐dependent fluorescent protein mt‐Keima (Katayama et al , 2011; Yamashita et al , 2016; Igarashi et al , 2020), which exhibits a short excitation in normal conditions (pH 8.0) and shifted to longer excitation wavelengths in mitophagy processes because of the acidic environment of the lysosome (pH 4.5). Flow cytometric analysis indicated that MITOL deletion significantly enhanced mitophagy, which was restored to normal levels by a low expression of MITOL.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that MITOL ubiquitinates and subsequently degrades Parkin in a proteasome‐dependent manner. To understand whether the ubiquitination of Parkin by MITOL has a functional effect on mitophagy, we performed quantitative analysis of mitophagy using the mitochondria‐localized pH‐dependent fluorescent protein mt‐Keima (Katayama et al , 2011; Yamashita et al , 2016; Igarashi et al , 2020), which exhibits a short excitation in normal conditions (pH 8.0) and shifted to longer excitation wavelengths in mitophagy processes because of the acidic environment of the lysosome (pH 4.5). Flow cytometric analysis indicated that MITOL deletion significantly enhanced mitophagy, which was restored to normal levels by a low expression of MITOL.…”
Section: Resultsmentioning
confidence: 99%
“…One compound, the anticancer drug gemcitabine, was identified as inducing mitophagy independent of Parkin ( Table 1 ) but dependent on MUL1. Gemcitabine caused the stabilization of PINK1 without reducing mitochondrial membrane potential ( 136 ).…”
Section: Pharmacological Enhancement Of Mitophagy: From Tool Moleculementioning
confidence: 99%
“…To reconcile these conflicting findings, we have to consider functional redundancy of other mitochondrial E3 ligases. Indeed, ARIH1/HHARI (Villa et al , 2017), March5 (Chen et al , 2017), MAPL/MULAN/GIDE/MUL1 (Ambivero et al , 2014; Yun et al , 2014; Li et al , 2015; Igarashi et al , 2020), p62‐keap1‐Rbx1 axis (Yamada et al , 2018), and HUWE1 (Di Rita et al , 2018) have been reported to mediate Parkin‐independent mitophagy. These E3s could compensate for PINK1/Parkin‐mediated mitophagy and conceal the output when the PINK1/Parkin function is inhibited.…”
Section: Introductionmentioning
confidence: 99%